Experimental investigation on thermal stratification induced by steam direct contact condensation with non-condensable gas. (25th May 2019) - Li, Weichao; Wang, Jianjun; Sun, Zhongning; Zhou, Yanmin; Liu, Jiaqing; Meng, Zhaoming
Highlights: Two condensation regimes of chugging and bubbling are observed. The maximum vertical temperature difference is about 60 °C. A small amount of air could make stratification pattern occur earlier and severer. Re-mixing pattern occurs when the bulk water temperature is close to 80 °C. Abstract: Thermal stratification induced by steam direct contact condensation is a significant technical concern to consider in the energy industry. Thirty experiments have been performed to investigate the effect of steam mass flux, bulk water temperature and air mass fraction on temperature distribution in the water pool. The condensation behavior and time evolution of temperature distribution are recorded and analyzed. Two condensation regimes of chugging and bubbling are observed. Three flow patterns, namely chugging-induced synthetic jets, steam-driven negative buoyancy jets and plume, are discussed. Three thermal patterns of mixing, stratification and re-mixing are identified. A small amount of air (1–2%) could make stratification pattern occur earlier and severer. The maximum vertical temperature difference is about 30 °C in pure steam experiments and 60 °C in mixture gas experiments. Re-mixing pattern occurs when the bulk water temperature is close to 80 °C. In addition, thermal penetration depth, the velocity of thermocline moving down and the thickness of thermocline are estimated through temperature data.